Acute caffeine ingestion enhances strength performance and reduces perceived exertion and muscle pain perception during resistance exercise - Duncan, M. J.; Stanley, M.; Parkhouse, N.; Cook, K.; Smith, M. (European Journal of Sport Science, 2013)
The efficacy of caffeine ingestion in enhancing aerobic performance is well established. However, despite suggestions that caffeine may enhance resistance exercise performance, research is equivocal on the effect of acute caffeine ingestion on resistance exercise performance. It has also been suggested that dampened perception of perceived exertion and pain perception might be an explanation for any possible enhancement of resistance exercise performance due to caffeine ingestion. Therefore, the aim of this study was to examine the acute effect of caffeine ingestion on repetitions to failure, rating of perceived exertion (RPE) and muscle pain perception during resistance exercise to failure. Eleven resistance trained individuals (9 males, 2 females, mean age±SD=26.4±6.4 years), took part in this double-blind, randomised cross-over experimental study whereby they ingested a caffeinated (5 mg kg-1) or placebo solution 60 minutes before completing a bout of resistance exercise. Experimental conditions were separated by at least 48 hours. Resistance exercise sessions consisted of bench press, deadlift, prone row and back squat exercise to failure at an intensity of 60% 1 repetition maximum. Results indicated that participants completed significantly greater repetitions to failure, irrespective of exercise, in the presence of caffeine (p=0.0001). Mean±S.D of repetitions to failure was 19.6±3.7 and 18.5±4.1 in caffeine and placebo conditions, respectively. There were no differences in peak heart rate or peak blood lactate values across conditions (both p >0.05). RPE was significantly lower in the caffeine compared to the placebo condition (p=0.03) and was significantly higher during lower body exercises compared to upper body exercises irrespective of substance ingested (p=0.0001). For muscle pain perception, a significant condition by exercise interaction (p=0.027) revealed that muscle pain perception was lower in the caffeine condition, irrespective of exercise. With caffeine, pain perception was significantly higher in the deadlift and back squat compared to the bench press. However, with placebo, pain perception was significantly higher for the deadlift and back squat compared to the prone row only. Therefore, acute caffeine ingestion not only enhances resistance exercise performance to failure but also reduces perception of exertion and muscle pain.